2013
DOI: 10.1007/s00167-013-2797-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the femoral insertion site of the medial patellofemoral ligament

Abstract: The adductor tubercle was clearly identified as an osseous landmark. The femoral insertion of the MPFL was approximately 10 mm distal to the adductor tubercle. These findings may improve understanding of the anatomy of the femoral insertion of the MPFL and may assist surgeons in performing anatomical reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
96
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 41 publications
4
96
0
4
Order By: Relevance
“…LaPrade et al 19 reported the MPFL center to be located 1.9 mm anterior and 3.8 mm distal to the ATT and 10.6 mm proximal and 8.8 mm posterior to the ME. Like Fujino et al, 16 we found the ATT to be the most easily discernable prominence in the vicinity of the MPFL attachment. The apex of the ATT was easier to identify than the ME, which was a broad, flat elevation on the medial femoral condyle.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…LaPrade et al 19 reported the MPFL center to be located 1.9 mm anterior and 3.8 mm distal to the ATT and 10.6 mm proximal and 8.8 mm posterior to the ME. Like Fujino et al, 16 we found the ATT to be the most easily discernable prominence in the vicinity of the MPFL attachment. The apex of the ATT was easier to identify than the ME, which was a broad, flat elevation on the medial femoral condyle.…”
Section: Discussionsupporting
confidence: 85%
“…Although variability in the ATT position was also observed in this study, its distance relative to the MPFL attachment was fairly consistent, averaging 7.9 6 1.2 mm. Fujino et al 16 reported this distance to be 10.6 6 2.5 mm. The current study marked anatomic structures with steel spheres and measured distances on radiographs, while Fujino et al 16 made measurements on CT scans.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Hence, it could be called the confluence point [19,23]. This point is posterior to the line extending from the posterior cortex of the femur (Figure 2)-more than 5 mm distal and posterior to Schöttle's point [23,24,25,26,27,28] (Figure 4). Interestingly, this point corresponds to the instant center of knee rotation.…”
Section: Introductionmentioning
confidence: 99%